2018
DOI: 10.1083/jcb.201706106
|View full text |Cite
|
Sign up to set email alerts
|

TRRAP is a central regulator of human multiciliated cell formation

Abstract: Multiciliated cells (MCCs) function to promote directional fluid flow across epithelial tissues. Wang et al. show that TRRAP, a component of multiple histone acetyltransferase complexes, is required for airway MCC formation and regulates a network of genes involved in MCC differentiation and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…TRRAP, a component of multiple histone acetyltransferase complexes was recently shown to be required for the initiation of the MCC gene expression program ‘downstream’ of the Notch signaling event (downstream in the same sense as described for Cdk2 above) ( Wang et al, 2018 ). TRRAP nuclear expression arises in prospective MCCs prior to Foxj1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…TRRAP, a component of multiple histone acetyltransferase complexes was recently shown to be required for the initiation of the MCC gene expression program ‘downstream’ of the Notch signaling event (downstream in the same sense as described for Cdk2 above) ( Wang et al, 2018 ). TRRAP nuclear expression arises in prospective MCCs prior to Foxj1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, genes that are mutated in human neonatal respiratory distress syndrome, such as those encoding surfactant proteins B and C, ABCA3 and the transcription factor FOXM1, have been shown to play key roles in alveolar development in mice ( Whitsett, 2014 ). The genetic manipulation of human adult airway epithelial cell cultures has also been used to identify transcription factors that are required for ciliated cell differentiation, and these are largely assumed to also function in the development of human embryonic airway ciliated cells ( Boon et al, 2014 ; Wang et al, 2018 ). However, until recently, experimental systems that allow a mechanistic investigation of the molecular regulation of human embryonic lung development have been available to only very few laboratories and progress has consequently been limited.…”
Section: An Introduction To Human Lung Developmentmentioning
confidence: 99%
“…The CDK1 and CEP164 interaction in the network could be explained by the fact that the ATM/ATR protein kinase phosphorylates CEP164 causing the activation of CHK1, which inhibits the cyclin-A-dependent activation of CDK1 and thus pauses the progression of the cell cycle [ 80 ]. We also observed the transactivation/transformation-domain-associated protein (TRRAP; regulator acting upstream of multicilin), which binds to upstream promoter region of several genes (associated with human ciliopathies) and regulate multi-ciliated cell differentiation and function [ 81 ]. Herceg and co-workers (2001) demonstrated that TRRAP is necessary for mitotic checkpoint and normal cell cycle progression.…”
Section: Structure and Composition Of The MCC Apparatus In Humansmentioning
confidence: 99%